Complementation between temperature-sensitive and deletion mutants of reovirus. - Spandidos, D A (1975)
A very low level of complementation has been found in conventional crosses between various classes of temperature-sensitive (ts) mutants of reovirus. A more definitive test for complementation was devised through a plaque assay on cell monolayers mixedly infected with defective reovirions lacking the L1 segment and prototype ts mutants from one or other of the known classes of reovirus mutants. An increase in the number of plaques on the mixedly infected plates over that on control plates infected with defective virions or ts mutants alone indicated that the ts mutant had been complemented by the defective virus. Class A, B, D, F, and G mutants were complemented at 39 C by the defective viruses, whereas class C and E mutants were not. In tests to determine whether complementation was reciprocal it was found that the defective virions were complemented by a class G mutant but not by the class C mutant. This and previous work (D.A. Spandidos and A. F. Graham, 1975) has therefore shown that of the seven known classes of ts mutants the class C mutant is the only one that neither complements nor is complemented by the defective virions. For this reason the class C ts mutation has been assigned to the L1 segment of the viral genome.